Coloring–decoloring behavior of fluoroalkyl end‐capped 2‐acrylamido‐2‐methylpropanesulfonic acid oligomer/acetone composite in methanol. Issue 12 (29th March 2013) - Kijima, Tetsushi; Nishida, Masakazu; Fukaya, Haruhiko; Yoshida, Masato; Sawada, Hideo
ABSTRACT A reddish‐brown fluoroalkyl end‐capped 2‐acrylamido‐2‐methylpropanesulfonic acid (AMPS) oligomer/acetone composite was prepared by heating the white oligomer powder with acetone at 80 °C for 3 h. The color was not observed in the corresponding non‐fluorinated AMPS oligomer/acetone composite, which was prepared under similar conditions. The coloring was probably caused by the formation of acetone polyaldol condensation products in the fluorinated oligomeric gel network cores. The colored RF‐(AMPS)n‐RF/acetone composite powders were stable and did not exhibit any color change after 2 years in natural light at room temperature. The colored composite powders dissolved in methanol to give a reddish‐brown solution at room temperature. However, the retro‐polyaldol condensation decolored the solution after 1 day at room temperature. This is the first example of the retro‐aldol polycondensation of acetone under mild conditions. The decoloration increased by between 38‐ and 70‐fold under UV irradiation, compared with that in dark conditions. The coloring–decoloring behavior was consistent and repeatable; therefore our fluorinated oligomer/acetone composites are promising candidates for new fluorinated coloring materials. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 2555–2564